2015
DOI: 10.5688/ajpe79220
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of Personality, Attitudes, and Study Skills on the Learning Curve within a Team-based Learning Environment

Abstract: Objective. To examine factors that determine the interindividual variability of learning within a teambased learning environment. Methods. Students in a pharmacokinetics course were given 4 interim, low-stakes cumulative assessments throughout the semester and a cumulative final examination. Students' Myers-Briggs personality type was assessed, as well as their study skills, motivations, and attitudes towards team-learning. A latent curve model (LCM) was applied and various covariates were assessed to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
17
0
3
Order By: Relevance
“…11 We also showed that preference for team learning was lower among students higher on the introvert scale, 16 and within the cohort of students, 50% of the students leaned towards introversion thus team-activities may have had lower preference. Although satisfaction in course evaluations still remain high, more work is needed to elucidate reasons for the relationship between grades, course format, and course evaluations.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…11 We also showed that preference for team learning was lower among students higher on the introvert scale, 16 and within the cohort of students, 50% of the students leaned towards introversion thus team-activities may have had lower preference. Although satisfaction in course evaluations still remain high, more work is needed to elucidate reasons for the relationship between grades, course format, and course evaluations.…”
Section: Discussionmentioning
confidence: 76%
“…A further change was made during the last year, where TBL was used for the first 9 weeks of class, covering all material. 16 The remainder of the course used cases to review material. In addition, lowstakes cumulative assessments were used (ie, assessments that cover all the course content and contribute to a small fraction of the overall course grade).…”
Section: Designmentioning
confidence: 99%
“…In 1970, Michaelsen designed TBL with the aim of increasing the quality of learning through employing problem-solving skills in an active and participatory learning environment ( 15 ). In other words, learners could achieve a higher level of cognitive learning by utilizing their personal knowledge in consulting with small groups ( 16 , 17 ). Some studies have emphasized the positive effect of TBL compared to the lecture method in medical education ( 18 – 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…27 Some negative aspects of TBL in the literature include increased preparation time by students and faculty members as well as student dissatisfaction (especially among introverted individuals and those who prefer the traditional faculty role of lecturing and storytelling). 25,27,30,31 Based on the literature review, faculty members teaching this course hypothesized that a change to a flipped team-based learning classroom would allow them to dedicate efforts towards discussing patient cases and relevant materials and answering student questions. This, in turn, would increase students' participation, enthusiasm, and interest in the course content.…”
Section: Introductionmentioning
confidence: 99%